2012
DOI: 10.4018/ijgbl.2012070104
|View full text |Cite
|
Sign up to set email alerts
|

Game Jams

Abstract: Game jams are events that allow game designers to develop innovative games in a time-constrained environment, typically within a 48-hour period during a weekend. Jams provide participants an opportunity to improve their skills, collaborate with their peers, and advance research and creativity in the field of game design. Having coordinated numerous jams locally and as one of the largest venues in the world for GGJ 2011, the authors present learned lessons on how to make these events into amazing collaborative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 8 publications
1
16
0
4
Order By: Relevance
“…Preston et al (2012) found that jammers on average have better academic performance than non-jammers, and that attending game jams are perceived as beneficial for improving skills, which also corresponds to Fowler et al's (2013a) finding. Reng et al (2013) described game jams as "an important learning space with characteristics known from communities of practice."…”
Section: Global Game Jammingsupporting
confidence: 55%
See 1 more Smart Citation
“…Preston et al (2012) found that jammers on average have better academic performance than non-jammers, and that attending game jams are perceived as beneficial for improving skills, which also corresponds to Fowler et al's (2013a) finding. Reng et al (2013) described game jams as "an important learning space with characteristics known from communities of practice."…”
Section: Global Game Jammingsupporting
confidence: 55%
“…To Turner et al, game designers are artists who create works, or games, whose focus is not about the commercialisation of the outcome, but the process of experiencing the creation of a game in a social context. Other motivations exist as well, including learning a new tool (Fowler et al 2013a), collaborate in a team environment for self-improvement (Preston et al 2012), or to be plain, "Getting a chance to make a game with other awesome people in a very short time" (Reng et al 2013). …”
Section: The Implicit Inspiration Networkmentioning
confidence: 99%
“…Of particular academic interest is the impact of the participation on those involved in these activities. Such research shows that participants can gain skills in prototyping and collaboration [30], can have a positive correlation with academic performance [31], and can improve confidence of participants [32]. Reng, Schoenau-Fog, and Kofoed [33], discuss the importance of the social aspect of the jam as highly important to the participants.…”
Section: B Academic Hackingmentioning
confidence: 99%
“…They have been identified as excellent opportunities for research in a wide variety of fields (Fowler et al, 2013a,b;Zook and Riedl, 2013;Ho et al, 2014), where time constraints encourage rapid and exploratory game design and development (Hrehovcsik et al, 2016). In addition, participants in game jams gain valuable skills in prototyping, collaboration (Preston et al, 2012;Fowler et al, 2013a,b), and collaborative learning (Shin et al, 2012;Arya et al, 2013). In a study exploring participants' motivations for participating in game jams, Zook and Riedl (2013) found that the majority set goals for personal benefit.…”
Section: Introductionmentioning
confidence: 99%